Encryption Implementation Paradigm for Digital Resource Management–An Overview - Kingsley O, Igboji,; Gabriel E, Ugwu (IJRDO -Journal of Computer Science Engineering, 2017)
Encryption is a process that “scrambles” data using sophisticated mathematical equations in order to protect it andkeep it private. This process transforms or encodes data in any form such as text, audio, video, graphics etc intoanother form it will be difficult to understand or interpret. Frequent illegal retrieval and utilization of digitalresources as enumerated above arouse the quest for a competent security artifact to eradicate the menace.Encryption key is not mere strings of text like passwords but are essentially blocks of gibberish, thusrequires a safe means to pass the key across to end users. Implemented algorithms encrypts original pieceuntil interested users meet certain obligations before access is granted with a decipher key. Research over the yearsadjudged this approach as a well structured routine in managing digitally embedded resources. A scenariofacilitated by utilizing IP authentication, digital certificate, signature and watermarking mechanisms toabate the rake been meted on digital resources. Encryption ostensibly creates a paradigm driven byevolving technological world.